Analysing the Shift in Prescribing Patterns: Sodium Glucose Co-transporter 2 Inhibitors, Dipeptidyl Peptidase 4 Inhibitors and Traditional Antidiabetic Drugs - Vini Pavithran; Pandiyan Balachandran; Chadappully Ismail Sajeeth; Athiappan Hariharan (Online Journal of Health & Allied Sciences)
India currently has around 77 million adults living with diabetes. Considering the growing impact of diabetes-related complications, we aimed to compare the real-world prescribing patterns of sodium-glucose cotransporter-2 inhibitors, dipeptidyl peptidase-4 inhibitors and traditional antidiabetics. Using a cross-sectional study design, the prescribing pattern and factors influencing the utilisation of the antidiabetic drugs, categorised by the HbA1c status, were assessed using the chi-square test. Of 260 eligible adults with mean [SD] age, 63.7[12.4] years; 54.7% of male participants initiated treatment with sodium-glucose cotransporter-2 inhibitors (n=27) or a dipeptidyl peptidase-4 inhibitors (n=31). The use of newer antidiabetic agents has steadily increased, with a slightly higher initiation rate in those over 65 years (21.5%). No significant difference was observed based on age (p = 0.182) or gender (p = 0.9548). Prescriber speciality had a significant impact (p = 0.00038). Cardiologists showed the highest shift towards newer drugs (36.5%). Prescriptions of newer antidiabetics have shown an upward trend over time, indicating a shift in prescribing practices. However, this increase was limited. Further efforts are necessary to identify and address the barriers to underutilisation of these drugs.